Using the critical speed concept to improve pacing strategy and 5K performance in distance runners: two case studies - Capello, K.; Wolff, L.; Kantor, M.; Pettitt, R.; Dexheimer, J. (The Journal of Strength and Conditioning Research, 2021)
Optimal pacing strategy is a major component of distance running performance, preventing premature fatigue while also ensuring maximal exertion by the end of the race. For the 5K race distance, most runners adopt one of 2 pacing strategies: either a U-shaped pattern characterized by a faster start and finish or a more evenly paced strategy with a final surge ("kick"). The critical speed (CS) concept is an under-utilized third strategy with the potential to predict and improve 5K performance. Purpose: The purpose of these case studies was to assess whether self-selected pacing strategy and 5K performance in experienced distance runners could be improved by prescribing a pace based on the CS concept from the 3-minute all-out exercise test (3 MT). Methods: A former and current collegiate distance runner (Runner #1: female; age: 23 years; height: 165 cm; weight: 54 kg; BF%: 20.4%; Runner #2: male; age: 19; height: 183 cm; weight: 59 kg; BF%: 5.8%) completed an initial 5K time trial on the track with individual lap splits given. They then completed a customized graded exercise test (GXT) for the attainment of peak maximum oxygen uptake (VO2peak) (Runner #1: 53.5 ml/kg/min; Runner #2: 58.0 ml/kg/min). This was followed by a 3 MT on the track for the attainment of CS and the finite capacity for exercise > CS, known as distance prime (D') (Runner #1: CS: 3.98 m/s; D': 144 m; Runner #2: CS: 4.17 m/s; D': 119 m). 5K time trial performance was predicted by the equation tLIM = (5000-D')/CS (Equation 1). The running speed associated with this tLIM was found by the equation S = D'/tLIM + CS (Equation 2). The runners were then instructed to run a second 5K time trial at the calculated speed. In addition to individual lap splits, the runners monitored accuracy to the prescribed pace using real-time speed feedback from a GPS watch. Comparisons were made between 5K #1, predicted time from CS and D', and 5K #2. Results: Runner #1: The finishing time for 5K#1 was 22:15 (7:10/mi, 8.4 mph). The predicted time based on Equation 1 was 20:19 (6:33/mi, 9.2 mph). The finishing time for 5K #2 was 21:35 (6:56/mi, 8.7 mph), which represents a 40-second improvement from 5K #1 and a difference of 76 seconds from the predicted time. Runner #2: The finishing time for 5K #1 was 22:00 (7:04/mi, 8.5 mph). The predicted time based on Equation 1 was 19:30 (6:16/mi, 9.6 mph). The finishing time for 5K #2 was 21:42 (6:59/mi, 8.6 mph), an improvement of 18 seconds from his initial 5K and a 162-second difference from the predicted time. Conclusions: Despite the subjects' experience at the competitive level, their self-selected pacing strategy was suboptimal compared to the prescribed pace from the 3 MT. Practical Applications: When performed properly, the 3 MT may enable athletes to run closer to their physiological potential by providing them with an individualized pacing strategy based on their unique CS/D' profile.